Effect Of The Double Walls On Thermal Internal Environment Of Buildings In Baghdad - Miqdad Haidar Al-Jawadi; Fatima Juma Edan (Iraqi Journal of Architecture and Planning, 2018)
the external walls represent one of the most important structural elements that have a direct effect on the thermal performance of the building.In order to achieve the aim of the research the experimental approach and style of analytical study were adopted. The current study included two main aspects: first, the theoretical side: Which included the time delay factor calculation and cooling load depending on the Radiant Time Series (RTS) theory that achieved accurate and detailed results and ease of application. While the second aspect included the practical test and measurement .The theoretical results achieved good convergence with practical results margin 22.3% increase at the expense of the electric power. Results of the study showed that the Exterior cladding material with large mass by using perforated brick of 120 mm thickness recorded the highest proportion of the economy in the amount of electric energy which considered to be the best thermally. However, Exterior cladding material (such as black Marble) and cladding materials with fewer block (such as composite- panel) represent the worst thermal performance because they made the lowest economic proportion of the amount of electric power . As well as, concluded that increasing the thickness of cavities from 25mm to 100mm may reduce the consumed amount of electric power about 4.3% .